Analisis Pemasaran Ayam Ras Pedaging di Kecamatan Rantau Utara - Revan Irwansyah; Media Agus Kurniawan (Bulletin of Community Engagement, 2024)
The purpose of this study was (1) to analyze the channel of broiler trading system in Rantau utara Distrct, (2) to analyze the amount of  share margin of the institution of broiler trading system in Rantau Utara District, and (3) to analyze the efficiency of broiler trading system in Rantau Utara District. There are 4 marketing channels for chickens, consisting of the first marketing channel where there are breeders and consumers, where consumers buy chickens directly from the breeders, in the second channel there is a chain of marketing channels where there are breeders, retailers and consumers and in the third channel there is the marketing channel. which involves collector farmers and consumers in channel IV involving retailer collector farmers and consumers, There are differences in margins for each marketing channel for broiler chickens in the 4 marketing channels, There are efficient chicken marketing channels in every marketing channel in North Rantau District with values below 30% considered efficient, in channel II %, in marketing channel III % and marketing channel IV %, The farmer's share value in the chicken marketing channel in Rantau Utara District reaches an efficient figure with a value of >40% considered efficient, in marketing channel II the farmer's share value is 78.9%, in marketing channel III 73.6% and in marketing channel IV 70%.